Teaching And Learning Activities Outside The Classroom to Improve The Quality of Learning For Students - Linta Wafdan Hidayah (Universitas Islam Madura, 2015)
Teaching and learning can become inherently spontaneous and student-centered when moved from the confines of the classroom into the world at large. From the collaborative learning atmosphere that results from the unique relationships developed outside the classroom, to the deep learning that occurs when students must put into practice “in the real world” what they have theorized about from behind a desk, field experiences are unmatched in their learning potential. Field experiences early in a student‟s career can be formative and can inspire students to continue in a field. The outside the classroom learning experience, commonly known as “field trip”, is a type of experiential learning which get students away from the formal classroom into a new environment. It can as simple as taking the class out on to the campus for a drawing exercise. Outside classroom activities can include summer field camps, extended stays at research stations and even a semester abroad.. the potential benefits for teaching and learning outside the classroom activities can be enormous . putting a class into a different physical setting generates a bond among class members and creates a learning community. Sometimes simply getting to the field trip destination is an opportunity for students to get to know each other, as well as their instructor. Active field trips can also offer unprecedented opportunities for experiential learning.